A comparative Efficacy of 635 nm and 980 nm Low-Level Laser Therapy in Treating Temporomandibular Disorders - Noor Qasim Mohammed; Zainab F. Mahdi; Balsam S. Abdulhameed (Iraqi Journal of Laser, 2025)
Background: Temporomandibular disorders (TMDs) are a complex group of conditions impacting the temporomandibular joint (TMJ) and masticatory muscles, leading to pain, reduced jaw mobility, and other debilitating symptoms. These conditions often result from multifactorial causes, including malocclusion, trauma, stress, and parafunctional habits. Effective treatment is challenging, necessitating innovative therapeutic approaches. Aim: This study compares the efficacy of two low-level laser therapy (LLLT) modalities with wavelengths of 635 nm and 980 nm in managing TMD symptoms. The goal is to determine which wavelength provides superior short-term and long-term therapeutic outcomes in pain relief, improved mouth function, and reduction of tender points. Materials and methods: Fifty patients with diagnosed temporomandibular disorder (TMD) were randomized into two groups. Group 1 received 635 nm low-level laser therapy (LLLT) , while Group 2 was treated with 980 nm low-level laser therapy( LLLT). Pain levels, mouth opening range, and the number of tender points were measured before each treatment and at a one-month follow-up. The treatment was administered in continuous mode, with a power output of 0.3 Watts (W). Irradiation time was 30 seconds per tender point, with a total of four treatment sessions (two sessions per week). A follow-up assessment was conducted one month after the completion of the treatment protocol. Data was analyzed using appropriate statistical methods to evaluate the efficacy of the treatments. Result: The 635 nm laser group experienced significantly greater reductions in pain intensity (p = 0.025) and fewer tender points in the masseter muscle (p = 0.048) compared to the 980 nm laser group during the short-term evaluation. However, no significant differences were observed between the two groups at the one-month follow-up. Conclusion: The 635 nm laser demonstrated superior short-term efficacy in reducing pain and masseter tender points, whereas both wavelengths were equally effective in the long term. These findings highlight the importance of wavelength selection in optimizing low-level laser therapy (LLLT) protocols for temporomandibular joint disorder (TMD) management. Further research is needed to explore the mechanisms underlying these differences and to identify the optimal parameters for sustained therapeutic outcomes.